Moxifloxacin (Avelox) Induced Thrombotic Thrombocytopenic Purpura - Sikander P. Surana; Zahily Sardinas; Alan S. Multz (Case Reports in Medicine)
We report a case of a 66-year-old African-American female who presented with complaints of progressively worsening weakness, shortness of breath on minimal exertion, lethargy for the last few days, and short episodes of aphasia lasting 20–30 seconds. Prior to presentation, she was treated with two courses of moxifloxacin for sinusitis. Laboratory examination was remarkable for anemia and thrombocytopenia with elevated lactate dehydrogenase and no evidence of renal failure. Peripheral smear showed numerous schistocytes and she was diagnosed with thrombotic thrombocytopenic purpura. Moxifloxacin was identified as the offending agent. The patient was treated with prednisone and plasmapheresis. To the best of our knowledge, this is the first reported case of thrombotic thrombocytopenic purpura associated with the use of moxifloxacin. Although rare, physicians should be aware of this serious complication associated with its use.